Wooden songs - Beneventi, Simone; Lang, David; Borzelli, Silvia; Svensson, Johan; Nova, Riccardo (Italy Stradivarius, 2020)
Wood is a primordial material. As such it contains life, both natural and human. To strike wood, to make it vibrate is the ancestral musical gesture second only to the rhythm of footsteps and breathing. No one can really know for certain, but without too many anthropological doubts, we can assume that the first non-body related instrument was a piece of wood. From that moment on human imagination has discovered countless ways of manipulating this many-sided material as a medium, ranging from constructing to music making. The wooden instrument is of profound cultural significance for the human race. The natural material has always been perceived by humans as an extension of the body. Take for example the stamping stick in the hands of a Master of Ceremonies: as the stick is hitting the ground the Master keeps the tempo for the chorus and the dancers, a primeval action for most music-oriented civilizations. Simone Beneventis research is focused on the wooden universe. He has collaborated with composers and master carpenters such as Giuseppe Bussi, ebony woodworker and conservator, creating and constructing wooden sound objects, many of which were made for the occasion.